A dynamic contact wear model of ball bearings without or with distributed defects. (December 2020) - Zhang, Xi; Xu, Hua; Chang, Wei; Xi, Hui; Pei, Shiyuan; Meng, Wei; Li, Huawei; Xu, Sining
A dynamic contact wear model of ball bearings consisting of wear degree and position distribution is proposed by integrating the developed contact wear model, multi-body dynamics and raceway waviness or ball diameter differences. Subsequently, the dynamic wear characteristics, not only for the ideal bearing under different axial and radial loads, but also for the bearing with above defects are analysed. The influences of load, typical waviness orders and amplitude on the wear of each ball against both raceways are evaluated and qualitatively validated. Finally, the dynamic characteristics of ball bearings with one ball larger are discussed, and then vibration frequency and wear rates distinction are verified by the experiment with working-surface roughness measurement as a way for wear rate assessment.